2018
DOI: 10.3390/nano8120987
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Thin Continuous GaSb Film on Si(001) by Solid Phase Epitaxy

Abstract: Nanocrystalline GaSb films were grown on Si(001) from the stoichiometric Ga–Sb mixture using solid-phase epitaxy at temperatures of 200–500 °C. Use of the solid-phase epitaxy method allowed the suppression of Ga surface diffusion and prevention of intense Sb desorption. At the annealing temperature of 300 °C, a 14-nm-thick GaSb film aggregates, while a 20-nm-thick GaSb film remains continuous with a roughness of 1.74 nm. A GaSb film with a thickness of 20 nm consists of crystalline grains with a size of 9–16 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
(57 reference statements)
1
4
0
Order By: Relevance
“…Film roughness is 6.7 nm. The result obtained corresponds to our previous data, 25) where it was shown that annealing of a stoichiometric thin GaSb film on Si(001) leads to the break of the film at an annealing temperature of more than 300 °C. Based on the position of the TO phonon peak of GaSb in the Raman spectrum of sample B (227.54 cm −1 ), we find that the lattice of GaSb islands is compressed by 0.16%, i.e.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Film roughness is 6.7 nm. The result obtained corresponds to our previous data, 25) where it was shown that annealing of a stoichiometric thin GaSb film on Si(001) leads to the break of the film at an annealing temperature of more than 300 °C. Based on the position of the TO phonon peak of GaSb in the Raman spectrum of sample B (227.54 cm −1 ), we find that the lattice of GaSb islands is compressed by 0.16%, i.e.…”
Section: Resultssupporting
confidence: 90%
“…GaSb grains with the same ratio were found earlier in a polycrystalline GaSb film grown by the same method on a Si(001) substrate. 25) Therefore, it can be approved that the smooth terraces found on the AFM image of the surface of sample A are polycrystalline GaSb SD1005-3…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…2a for 2 values from 68.3° to 69.0° (close to the principal peak) presents a small left shoulder related to the GaSb crystallization in the same direction of the substrate. This kind of substrate influence has been studied by Chusovitin et al 36 in GaSb thin films synthesized via solid-phase epitaxy.…”
Section: Resultsmentioning
confidence: 98%
“…The process becomes more complicated in the case of compound semiconductor growth, since the binding energies of adsorbate atoms both to the substrate and in the compound itself, should be considered. According to [29,30] a continuous GaSb film is formed on a Si substrate at a low annealing temperature. A subsequent increase in temperature turns it into islands due to a large discrepancy between the lattice parameters of the substrate and the film [31], which is undesirable in the formation of continuous GaSb films [32].…”
Section: Resultsmentioning
confidence: 99%